Economic Modeling of Residual Generation for the Lingayen Gulf Watershed - McGlone, Douglas; Caringal, Herminia (Science Diliman: A Journal of Pure and Applied Sciences; Vol 12 No 2 (2000), 2007)
The Philippines is one of four countries involved in the Southeast Asian core project of LOICZ (Land Ocean Interactions in the Coastal Zone) which has among its general goals the determination of how changes in human activities affect the fluxes of materials between land, sea, and atmosphere through the coastal zone. The economic component of the Philippine project addresses the question: “How does a change in economic activity affect coastal waters?” Of particular concern is the introduction of anthropogenically-derived residuals (N, P, C, SS) into coastal waters. A regional input-output (IO) model for Region 1 of the Philippines has been developed to estimate how projected changes in economic activity may affect residual flows into Lingayen Gulf. A residual coefficient matrix, derived from information obtained with a rapid assessment model (RA) of residual generation in the Lingayen Gulf watershed, has been incorporated into the IO model. Such a model allows for analysis of various economic scenarios for the region, with projections of residual generation as the output. The resulting changes in residual flows may then serve as inputs to biogeochemical models of Lingayen Gulf. From this process, the impact of various economic scenarios on the water quality of Lingayen Gulf may be ascertained. This paper discusses and compares the RA and IO models of residual generation for the Lingayen Gulf watershed and provides examples of the scenario analysis process.
Keywords: economic modeling, Lingayen Gulf, rapid assessment watershed, residual generation